A systematic review and meta-analysis of the impact of collaborative practice between community pharmacist and general practitioner on asthma management - Mubarak, Naeem; Zin, Che Suraya (2018)
Objective: To evaluate the impact of collaborative practice between community pharmacist (CP) and general physician (GP) in asthma management.